New functions of Ctf18-RFC in preserving genome stability outside its role in sister chromatid cohesion. - Lionel Gellon; David F Razidlo; Olive Gleeson; Lauren Verra; Danae Schulz; Robert S Lahue; Catherine H Freudenreich (PLoS Genetics, 2011)
Expansion of DNA trinucleotide repeats causes at least 15 hereditary neurological diseases, and these repeats also undergo contraction and fragility. Current models to explain this genetic instability invoke erroneous DNA repair or aberrant replication. Here we show that CAG/CTG tracts are stabilized in Saccharomyces cerevisiae by the alternative clamp loader/unloader Ctf18-Dcc1-Ctf8-RFC complex (Ctf18-RFC). Mutants in Ctf18-RFC increased all three forms of triplet repeat instability--expansions, contractions, and fragility--with effect over a wide range of allele lengths from 20-155 repeats. Ctf18-RFC predominated among the three alternative clamp loaders, with mutants in Elg1-RFC or Rad24-RFC having less effect on trinucleotide repeats. Surprisingly, chl1, scc1-73, or scc2-4 mutants defective in sister chromatid cohesion (SCC) did not increase instability, suggesting that Ctf18-RFC protects triplet repeats independently of SCC. Instead, three results suggest novel roles for Ctf18-RFC in facilitating genomic stability. First, genetic instability in mutants of Ctf18-RFC was exacerbated by simultaneous deletion of the fork stabilizer Mrc1, but suppressed by deletion of the repair protein Rad52. Second, single-cell analysis showed that mutants in Ctf18-RFC had a slowed S phase and a striking G2/M accumulation, often with an abnormal multi-budded morphology. Third, ctf18 cells exhibit increased Rad52 foci in S phase, often persisting into G2, indicative of high levels of DNA damage. The presence of a repeat tract greatly magnified the ctf18 phenotypes. Together these results indicate that Ctf18-RFC has additional important functions in preserving genome stability, besides its role in SCC, which we propose include lesion bypass by replication forks and post-replication repair.